2020
DOI: 10.1161/strokeaha.119.028713
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clopidogrel for Prevention of Stroke Based on CYP2C19 Allele Status in the POINT Trial

Abstract: Background and Purpose: Clopidogrel is an antiplatelet drug that is metabolized to its active form by the CYP2C19 enzyme. The CHANCE trial (Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events) found a significant interaction between loss-of-function allele status for the CYP2C19 gene and the effect of dual antiplatelet therapy with aspirin and clopidogrel on the rate of early recurrent stroke following acute transient ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Pharmacogenetic testing can identify patients with clopidogrel resistance, however, its clinical implications for stroke prevention practice are unclear at this time. [38][39][40] Another short-term dual antiplatelet treatment option is the combination of daily low-dose aspirin and ticagrelor, a P2Y12 antagonist most often used in coronary artery disease. The Acute Stroke or Transient Ischemic Attack Treated With Ticagrelor and ASA for Prevention of Stroke and Death (THALES) trial tested a 30-d course of the aspirin-ticagrelor combination starting within 24 h of a high-risk TIA or minor ischemic stroke.…”
Section: Diabetes Screening and Assessmentmentioning
confidence: 99%
“…Pharmacogenetic testing can identify patients with clopidogrel resistance, however, its clinical implications for stroke prevention practice are unclear at this time. [38][39][40] Another short-term dual antiplatelet treatment option is the combination of daily low-dose aspirin and ticagrelor, a P2Y12 antagonist most often used in coronary artery disease. The Acute Stroke or Transient Ischemic Attack Treated With Ticagrelor and ASA for Prevention of Stroke and Death (THALES) trial tested a 30-d course of the aspirin-ticagrelor combination starting within 24 h of a high-risk TIA or minor ischemic stroke.…”
Section: Diabetes Screening and Assessmentmentioning
confidence: 99%
“…In the POINT trial, presence of a clopidogrel slow metabolizer genetic variant was not associated with a significant reduction in efficacy, but there was a trend towards lower efficacy in these patients, although this did not reach significance due to the small sample size. 37 Following the results of these two trials, the combination of aspirin and clopidogrel is now recommended for patients with recent minor (NIHSS score ≤3) noncardioembolic IS or high-risk TIA (ABCD2 score ≥4). It should be started early (ideally within 12–24 h of symptom onset and at least within 7 days of onset) and continued for 21–90 days.…”
Section: A: Appropriate Antithrombotic Therapymentioning
confidence: 99%
“…CYP2C19 allele status is considered as a possible determinant of the clopidogrel efficacy but still the relation is not yet clearly established. 44,45 Neuroinflammation is considered an important pathophysiological mechanism of cerebral damage in AIS. Experimental studies related to inflammation-modulating agents have shown promising results but failed in clinical trials.…”
Section: Tr In Aismentioning
confidence: 99%